Effect of ensiling and organic solvents treatment on proteolytic enzymes of layer chicken intestine - Rathina Raj, K. (Springer-Verlag, 2010)
Effect of ensiling and organic solvents on the protein extractability and on the activities of the proteolytic enzymes of layer chicken intestine was evaluated. The protein content of water extract of layer chicken intestine was 2.45 mg/ml. Highest proteolytic activity (26.3 units) was observed at pH 10.6 and lowest at pH 6.8 (7.2 units). Higher acidic proteolytic activities were observed at pH 2.4, pH2.8 and at pH 5. Acid ensiling resulted in 65.6% reduction in acidic protease activity compared to 57.4% reduction by fermentation ensiling. Neutral and alkaline protease activities were also reduced up to a maximum of 41.8% and 46.5%, respectively. A ratio of 1:1.5 of cold acetone to intestine homogenate was found best for enhancing the neutral and alkaline protease activity. The study revealed that layer chicken intestine is a rich source of proteases especially of neutral and alkaline proteases, which could be harvested for commercial purposes and both acid and fermentation ensiling of layer chicken intestine resulted in reduction of protein extractability and enzyme activity. Treatment with acetone almost doubled the activities of neutral and alkaline proteases compared to initial values in water extract of fresh intestines.